Determinant Factors of Street Vendor's site in North Babarsari Street, Depok, Sleman, Yogyakarta - Subroto, T. Yoyok Wahyu (Department of Architecture And Planning, Faculty of Engineering, Universitas Gadjah Mada, 2010)
The migration of villagers to the city contributes the city's problems. Most of these urbanized people work in the informal sector such as blue-collar worker, hawker and street vendors. North Babarsari street is the connector of various center of activities area such as education, commerce and government. It makes this street becomes very busy and strategic. This street connects both street as Adisucipto street and North Ring-Road while at the eastern part of this street the campus estates are located.The method of this research refers to the physical setting behavior which directed to see the element of activities setting. It is also directed to see the factors that relate to the setting of the street vendors. The data analysis resulted that there are four determinant factors that influence the location of street vendors site such as (a) shading element (trees); (b) types of comodity/goods; (c)built street furniture and (d) working time.